Source, Sample Preparation, Analytical and Inhibition Methods of Polycyclic Aromatic Hydrocarbons in Food (Update since 2015). Issue 4 (2nd October 2022) - Yan, Xiao-ting; Zhang, Yuan; Zhou, Yu; Li, Guo-hui; Feng, Xue-song
ABSTRACT: Polycyclic aromatic hydrocarbons (PAHs), as a group of carcinogenic and mutagenic substances, have raised intense concern among the global community due to their ubiquitous occurrence. It has been reported that food is also a key source of human exposure to PAHs because they can enter the food chain in different ways. Therefore, it is necessary to develop accurate analysis methods for such compounds in food samples to ensure food safety and human health. This paper aims to review the state-of-the-art purification techniques and determination methodologies for PAHs in comprehensive food samples. Different extraction methodologies and analytical approaches are updated, elaborated upon and discussed, particularly innovative, rapid, efficient and ecofriendly ones. In addition, this review discusses the latest results about the sources and interventions of PAHs contamination in food products.